Examination of whole lengths of coronary arteries by color flow echocardiography - Al-Ashwal, Nashwan Saleh Mohammed (Journal of medical and pharmaceutical sciences, 2022)
Introduction: increased cases of cardiac diseases in our world, and the absence of non-invasive, accurate, and feasible method of examination necessitate the looking for one’s which achieved these criteria, that is the visualization of the coronary arteries (CAs) by means of the color flow transthoracic echocardiography. Aim of work: To check the possibilities of color flow mode of Transthoracic Echocardiography for seeing the whole lengths of coronary arteries and areas of stenosis, dilatations, and possibilities of visualization of collateral vessels. Materials and Methods: In Adhale governorate, Yemen republic, an observational study was conducted at Dr. Nashwan Al-Ashwal Clinic for medical and cardiac diseases. Cases were selected randomly. The total number of them was 763 participants, 700 males and 63 female ranging from 5 months to 70 years old, and then divided into two groups; 228 control and 535 patients. Period of study was from 1st January to 31th December 2021. The collected information was entered into Microsoft excel and word. Technique of examination by using of routine transthoracic echocardiography and the color flow mode with adjustments of its parameters as explained in the context. Results: A success in visualization of the whole lengths of coronary arteries in all patients (100%), in addition to some other features also were seeing, as the following: "group 1" few areas of beaded shape scattered along the vessel course, and one or two blue segments connecting the red vessel end to end of the same artery, and small area/areas of either red or blue colors with network shapes, while in "group 2"; there are more beaded areas, more than two areas of mosaic color reflections (stenosis), arterial segment/segments with dilatation, more than two blue segments of short or long distances that connecting end to end of the same red (artery) vessel and to another vessel/vessels, local and diffused color changes in the blue (collateral arteries or connector vessel) or red vessels to tint white or yellow colors respectively, large areas of either red or blue color (network arteries), blood pooling focus that pumping blood into more than one areas distal to level/levels of coronary arteries stenosis, and lastly, appearance of a darken area/side in the left ventricle. decreased in /absence of blood vessels, particularly, the red ones, in few patients with severe ischemic dilated cardiomyopathy. Conclusion: The examinations by color flow mode of transthoracic echocardiography permits the visualization of whole lengths of coronary arteries, stenotic and dilated segments, in addition to the small coronary arteries and the collateral vessels or rescuing circulation, and discovered that the collateral circulation is in needs for higher pressure in the pre stenotic segments, to open their vessels one by one, and also to facilitate blood flowing through the stenotic segments before development of collateral circulations, that also affected by atherosclerotic changes, and leads to arise of blood pooling focus.